Glaciogenic and volcanic rocks, evaporites and coal in the Maritimes Basin of eastern Canada and variable low-latitude climate during the Late Paleozoic Ice Age - Giles, Peter S. (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2025)
The depositional record in the Maritimes Basin falls entirely within the Late Devonian to Permian span of the Late Paleozoic Ice Age (LPIA). Basin paleolatitudes range from 25–27°S in the middle Tournaisian to equatorial by the end of the Carboniferous. Evidence for glaciation reaching below 10° in latitude is recorded in uppermost Carboniferous to lowermost Permian rocks of the western USA. Sedimentologic evidence for cold-climate sedimentation within the Maritimes Basin is documented in Nova Scotia for the first time by glacially faceted and striated clasts in upper Tournaisian diamictites, which are coeval with glacial diamictites recently described in western Newfoundland. Marine fossils in immediately underlying upper Tournaisian rocks and coeval thick evaporites drilled in the Gulf of St. Lawrence suggest deposition under warm arid conditions. Other Maritimes Basin evaporites were typically deposited during isotopically predicted warm (and arid) climate excursions except for the middle Tournaisian Gautreau Formation, in which glauberite salts indicate seasonal freezing. Late Carboniferous coals were deposited globally during the coldest times of the LPIA and Maritimes Basin coals may record the same paleoclimatic setting. Mississippian volcanism in the Maritimes Basin shows linkages with warm paleotemperature excursions in the isotope record and the associated retreat of ice sheets, as well as sea-level rise within the LPIA. Mississippian rocks in the Maritimes Basin record warm climatic conditions that are consistent with the basin’s low-latitude position, but they also record cold-climate settings that have been overlooked due to a long-standing low-latitude “paleotropical” climate bias.